2021
DOI: 10.2147/vmrr.s285165
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Infection of Fascioliasis andTrypanosomosis and Associated Risk Factors in Local Zebu Breed Cattle of Western Ethiopia

Abstract: Background A cross-sectional study was conducted from late October 2016 to June 2017, with the primary objective of estimating and analyzing the concurrent occurrence of both fascioliasis and trypanosomosis infections and associated risk factors along the tsetse-infested Didessa river basin. Methods The methodology applied was based on stratified sampling for the parasitological study, with entomological and malacological surveys, including fly dissection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…The result was shown on (Table 5). Our ndings are in line with the ndings of Meharenet and Shitu (2021), who found that the medium conditioned animals were more infected in Ethiopia. However, our ndings were in contrast to that of Uwalaka et al (2019), who reported a higher prevalence among poor conditioned animals in Abia state, Nigeria.…”
Section: Resultssupporting
confidence: 93%
“…The result was shown on (Table 5). Our ndings are in line with the ndings of Meharenet and Shitu (2021), who found that the medium conditioned animals were more infected in Ethiopia. However, our ndings were in contrast to that of Uwalaka et al (2019), who reported a higher prevalence among poor conditioned animals in Abia state, Nigeria.…”
Section: Resultssupporting
confidence: 93%